2016
DOI: 10.1063/1.4963741
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of physical conditions of boron uptake region in proton boron fusion therapy (PBFT)

Abstract: We conducted a quantitative study to identify the effectiveness of proton boron fusion therapy (PBFT). Four simulation scenarios were designed to investigate the escalation in total dose with the proton boron reaction using a Monte Carlo n-particle extended (MCNPX 2.6.0) simulation. The peak integrated dose was obtained for three different physical conditions (i.e., boron uptake region (BUR) thickness, BUR location, and boron concentration) with differing proton beam energy (60–90 MeV). We found that the peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…And also how much is the proton dose enhancement by the produced alpha particles? In fact, the current study contests the results of specific literatures 1,[3][4][5] in terms of physical scientific basis and validity of the MCNPX simulation. Therefore, the cross section of the 11 B(p,α)2α reaction, as well as simulation of interaction between proton beam and a BUR inside a water phantom, was investigated.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…And also how much is the proton dose enhancement by the produced alpha particles? In fact, the current study contests the results of specific literatures 1,[3][4][5] in terms of physical scientific basis and validity of the MCNPX simulation. Therefore, the cross section of the 11 B(p,α)2α reaction, as well as simulation of interaction between proton beam and a BUR inside a water phantom, was investigated.…”
Section: Introductionsupporting
confidence: 68%
“…The proton beam energy in our study was 80 MeV that is similar to 1,3-5 the 80-MeV 1 ; 60-, 70-, 80-, 90-MeV 3 ; 60-to 120-MeV 4 ; 75-to 85-MeV 5 protons that were used in the mentioned papers. Furthermore, they used pure 11 B cubics 1,3,4 as proton dose booster, which was done in the current work as well. However, no enhancement was seen in the proton 'dose' that has a full agreement with the physical basis of the low cross-section fusion of 11 B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proton captures 11-boron ( 11 B), resulting in three alpha particles (one 3.76 MeV, two 2.46 MeV) and a 719 keV prompt gamma ray [ 6 , 8 ]. Theoretically, as BNCT generates one alpha particle after the final reaction, the therapeutic effect of PBFT per incident particle is three times greater than that of BNCT [ 9 ]. In addition, based on data from our previous studies, we confirmed that the therapeutic effect of PBFT can be improved by as much as 1.5 times compared to that of a proton beam without a boron compound [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%